Mesophilic and thermophilic anaerobic digestion of lipid-extracted microalgae N. gaditana for methane production. (May 2017) - Capson-Tojo, Gabriel; Torres, Alvaro; Muñoz, Raúl; Bartacek, Jan; Jeison, David
Abstract: In the last years, a huge effort has been made to make biodiesel production from microalgae a feasible option. Besides the potential of biodiesel for replacing fossil fuels as a cleaner alternative, some limitations have still to be overcome. Among them, the low energy yields of the process and the high-energy requirements of the harvesting and drying steps lead to a high cost per litre of fuel. In this context, anaerobic digestion of the microalgal biomass after lipid extraction can improve the energy balance of the process, by producing methane and revalorizing a waste generated during biodiesel production. In this study, the production of biogas by anaerobic digestion of the marine microalgae Nannochloropsis gaditana after oil extraction was studied. As the hydrolysis is known to be the rate-limiting step of anaerobic digestion of solid substrates, the influence of the process temperature on this step was assessed. For this purpose, two different anaerobic sludges, i.e. mesophilic (35 °C) and thermophilic (55 °C), were used as inocula for different batch tests and for two continuous anaerobic bioreactors. The influence of the oil extraction process on the structural integrity of the microalgae was also studied. The results obtained from scanning electron microscopy and flow cytometry showed that the lipid extraction did not cause cell lysis, but the structure of their surface was affected by the process. Batch assays showed that thermophilic conditions did not improve the biomethane potentials when compared to mesophilic conditions. Two continuous anaerobic bioreactors operated for 120 days confirmed the batch results. However, measurements of the chemical oxygen demand showed that the soluble fraction in the thermophilic reactor was higher than under mesophilic conditions, indicating an improved hydrolysis step. This was confirmed by the results of scanning electron microscopy and flow cytometry, which suggested a more intense disintegration of microalgae in the thermophilic reactor, indicating a greater degree of hydrolysis. Nevertheless, this advantage of thermophilic temperatures over mesophilic conditions did not improve the methane productivity. Highlights: The effect of temperature and lipid extraction on biomethane production was studied. Lipid extraction affected the structure of the surfaces of the microalgae. A higher degree of hydrolysis was observed at thermophilic temperature. No significantly different methane yields were found at both temperatures.